IMPLEMENTASI STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK PEROLEHAN BELAJAR KONSEP NORMA DI SMP - Mustaan, Mustaan; Aunurrahman, Aunurrahman; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This study aims to (1) find the Pancasila and Civic Education learning plan using problem solving strategy, (2) to describe the implementation of Pancasila and Civic Education learning using problem solving strategy, (3) to describe learning evaluation with problem solving strategy, and (4) to describe the learning achievement of students in achieving the acquisition of learning the concept of norms in the learning of Pancasila and Civic Education by using problem solving strategy in classÂ SMP This research is a qualitative descriptive research to study